Resolution of the First Ukrainian endometriosis forum "Drug treatment for endometriosis-associated pelvic pain. The quality of a woman's life" - A.V. Boichuk; D.G. Herman; Y.O. Dubossarska; N.F. Zakharenko; L.V. Kalugina; N.V. Kosei; S.I. Reheda; N.M. Rozhkovska; T.F. Tatarchuk; O.V. Trokhymovich; O.G. Yashina; N.V. Yarotska (Publishing House TRILIST, 2023)
Endometriosis affects 10% of all women of reproductive age, i.e. 190 million patients. Ukraine currently does not gather statistics on the incidence of endometriosis, but, at a rough estimate, this number is approximately 280 thousand women and the real number may be higher. Endometriosis has known significant social, medical and economic impact. Therefore, Ukrainian leading specialists in obstetrics and gynecology focus on new treatments for endometriosis, given current scientific data and the needs of patients. The given resolution and algorithms for treatment for endometriosis are the common stand of leading specialists in gynecology in our country and were developed on the basis of modern domestic and foreign data and current clinical guidelines. This resolution aims to improve clinical approaches to the routine practice of treatment for endometriosis. The constant increase in the incidence of endometriosis and its management characteristics allows to conduct an extensive study of the effectiveness and safety profile of various progestogens. In recent years, a number of further evidence have appeared regarding dydrogesterone treatment for endometriosis. New data on the effectiveness of dydrogesterone offer another hormone-based treatment for endometriosis, which is extremely important given the need for long-term and individualized treatment for endometriosis. The Europ ean Society of Human Reproduction and Embryology (ESHRE) states that the degree of pain relief in endometriosis is the same for all hormone-based treatments, but the safety and tolerability profiles of different medicinal products differ, which must be considered. According to the obtained data on the effectiveness and metabolic safety profile of various progestogens and during the discussion, algorithms for dydrogesterone-based treatment for endometriosis were proposed.